Gender differences and construct of the early adolescent's emotional intelligence - Naghavi, Fataneh; Redzuan, Ma'rof; Asgari, Arezoo; Mirza, Mojgan (Marsland Press, 2012)
The emotional intelligence construct is a rather novel concept with little empirical support, particularly, in relation to the link between gender and the early adolescent’s emotional intelligence. Hence, the specific objective of this research is to determine the relationship between gender and early adolescent’s emotional intelligence (EQ). EQ is a set of abilities such as conception, emotion appraisal and expression, emotion management and regulation, and emotion utilization of emotion. The present study was carried out among 234 Iranian students in the second and grades of guidance schools (age 12-15) in Tehran, Iran. The students (girls and boys) were clustered through random and multistage sampling. Data were collected using the Schutte’s (1998) Emotional Intelligence Scale. T-test indicates that there is a statistical significant difference between emotional intelligence among boys and girls.